22 DIFFUSE PULMONARY MILIARY LESIONS: A CASE REPORT OF THYROID CARCINOMA AS THE UNSUSPECTED CAUSE. (1st January 2006) - Kong, M.; Clancy, J. P.; Ruiz, F.; Winkler, M.
Abstract : Purpose: To highlight the need for pediatricians to have an awareness of metastatic thyroid carcinoma in the differential diagnosis of pulmonary miliary lesions by presenting an unusual case presentation. Method: We report a previously healthy 4-year-old female patient with a 9-week history of persistent cough and exertional dyspnea associated with decreased appetite and weight lost. The review of systems was positive for exposure to Mycobacterium tuberculosis in her first year of life from her biological mother but otherwise negative. Her physical exam was notable for bilateral cervical lymphadenopathy, with the largest node measuring approximately 5 3 4 cm. Thyroid exam was normal. Chest roentgenogram revealed diffuse nodular densities in both lung fields. An extensive diagnostic work-up was undertaken to identify Mycobacterium tuberculosis as the causative agent. A skin PPD test was nonreactive and gastric lavages failed to identify acid fast bacilli with Ziehl-Neelsen stain and direct fluorescent antibody. Silver stain for fungal elements and HIV titers were also negative. A subsequent lung bronchoscopy revealed compression of the left lung bronchus and microscopic analysis of the bronchoalveolar lavage fluid demonstrated normal cellular distribution with no microbial pathogens. A fine-needle biopsy of her cervical lymph node revealed metastatic thyroid carcinoma. The metastatic nature of the miliary pulmonary lesions was confirmed by avid uptake of radioactive iodine by the lesions. Results: Thyroid carcinoma is uncommon in the pediatric population, with an annual incidence of 0.02-0.3 cases per 100, 000 population. It typically manifests as an asymptomatic mass in 60-80% of cases and often presents with advanced disease in children. Extensive regional nodal involvement has been reported in up to 70% of pediatric patients with distant metastasis to the lungs, bone, or liver present in 10-20% of patients. Diffuse miliary spread to the lungs is unusual, with bilateral total lung involvement reported only in several cases. Conclusion: During the evaluation and diagnosis of diffuse interstitial lung lesions in pediatrics, it is important to identify any suspected infectious pathogens. When an infectious etiology is not identified, examination of tissues by nodal and/or lung biopsy is often necessary to confirm the diagnosis. Miliary dissemination of thyroid carcinoma is an unusual cause of diffuse interstitial nodular pulmonary infiltrates.